Emotional Communication on Christian WeChat Official Accounts During the COVID-19 Pandemic in the First Half of 2020 - XU, Guiquan; LIU, Yage (Journal of Research for Christianity in China (JRCC), 2025)
This paper examines the emotional communication strategies employed by Christian WeChat public accounts during the first half of 2020, using their information dissemination as a case study. It explores how these religious media channels conducted emotional communication during the 2020 pandemic and the specific roles they played in social emotional governance. Content analysis reveals that emotional elements are prominent in the information dissemination of Christian WeChat public accounts, with positive emotions overwhelmingly dominant. In confronting the pandemic, these accounts served a dual purpose: on one hand, they provided emotional reassurance, encouraging audiences to maintain a positive mindset; on the other hand, leveraging the introspective nature of Christian emotional communication, they guided audiences toward self-reflection and called for prayers for the pandemic. Text analysis reveals four emotional communication strategies employed by Christian public accounts: - Emotional resonance through conversational tone - Rational emotional communication via faith instruction - Humanistic emotional outreach through universal care - Traffic-driven emotional agitation While a few commercially driven personal accounts leaned toward emotional agitation, the other three strategies demonstrated positive emotional guidance.